Clinical significance of androgen receptor in unilateral invasive breast cancer in women - Menghan Cao; Di Pan; Yuqi Li; Zicheng Pei; Runbang Wang; Bo Zhang; Chaorong Bian; Qinghao Gu; Pengfei Qu; Chenchen Yu; Haonan Liu; Zhengxiang Han (European Journal of Medical Research)
Abstract Objective To assess the prognostic relevance of androgen receptor (AR) expression in patients following modified radical surgery for invasive breast cancer. Methods A cohort of 515 patients who underwent modified radical mastectomy for breast cancer from July 2016 to November 2017 was analyzed. Immunohistochemistry was employed to determine the expression levels of AR, estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor-2 (HER-2), cell proliferation nuclear antigen (Ki-67), oncogene (P-53), cytokeratin 5/6 (CK5/6), topoisomerase-2 (TOPO-2), and epidermal growth factor receptor (EGFR). The correlation between AR expression and clinicopathological features as well as prognosis was examined. Multifactorial analysis using Cox proportional risk regression identified independent prognostic factors for disease-free survival (DFS), and a nomogram model was developed based on these factors. Results Patients in the AR-positive group demonstrated a significantly higher frequency of low histologic grade (grade 1–2), ER positive, PR positive, TOPO-2-negative, CK5/6-negative, and EGFR-negative as compared to the AR-negative group (P < 0.05). Among ER( +)/HER-2(−) and ER( +)/HER-2( +) patients with breast cancer, AR-positive individuals exhibited prolonged DFS (P < 0.05). Conversely, in ER(−)/HER-2( +) and ER(−)/HER-2(−) patients with breast cancer, AR expression did not significantly influence disease-free survival (P > 0.05). Multifactorial regression analysis identified AR/ER ratio, histological classification, and lymph node metastasis as independent prognostic factors for DFS (all P < 0.05). The developed nomogram model underscored the significance of histological classification as the primary predictive factor for patient outcomes, followed by AR/ER ratio and lymph node metastasis Conclusion AR expression holds varying prognostic implications across different breast cancer subtypes, with AR positivity indicating a favorable prognosis, particularly in ER-positive tumors.